The imperial Irish : Canada's Irish Catholics fight the Great War, 1914-18 - McGowan, Mark George, 1959- (McGill-Queen's studies in the history of religion., 2017)
"From 1914 to 1918, tens of thousands of Canadian Catholic men and women of Irish descent or birth rallied to the Empire's call to arms against Germany and its allies. Bishops, priests, Catholic newspaper editors, and Irish Catholic politicians from across Canada publicly supported Government efforts to win the war. Despite these actions, non-Catholic Canadians continued to doubt the loyalty of Irish Catholics. The neutrality of Pope Benedict XV, the supposed pro-Austrian sympathies of many Catholic new Canadians from central Europe, Irish republicans who fomented rebellion in Ireland, and the perceived indifference to the war by French Canadian Catholics, collectively painted all Catholics in a negative light. Catholic leaders and rank-and-file Irish Catholics in Canada struggled on two fronts during the Great War: fighting the Empire's enemies in Europe, and defending themselves against charges of disloyalty at home, because of persons and issues beyond their control. In this second struggle Irish Catholics had to be sensitive to their French Canadian co-religionists, making clear their loyalty to Canada and the Empire without completely alienating them. At the same time Irish Catholic leaders maintained that they had a double duty--a duty to Canada as a member of the British Empire, and a duty to see that Ireland was given the type of self-government that they as Canadians enjoyed. Grounded in research from dozens of archives, census data, and personnel records, this book explores conflicts which threatened to irreparably divide Canada along religious and linguistic lines."--